Earth-air Heat Exchangers For Passive Air Conditioning: Case Study Burkina Faso - Woodson, Thomas; Coulibaly, Yézouma; Traoré, Eric Seydou (Penerbit Universiti Sains Malaysia, 2012)
An earth-air heat exchanger (EAHX), also known as an earth tube heat exchanger or Canadian well, is a system for cooling and heating buildings using the ground as a heat sink/source. This study examines the ground temperature gradient and the performance of an EAHX performance in Burkina Faso. Ground temperature measurements were made at depths of 0.5 m, 1.0 m and 1.5 m. At the hottest time of the day, 15:00, the average outside temperature was 39.0°C, but the average temperature 1.5 m underground was 30.4°C. A clear phase shift was observed between the maximum outside temperature and the maximum ground temperature: the time of the day when the outside temperature is highest corresponds to the time when the underground temperature was lowest. The EAHX was 25 m long, 1.5 m underground and used a 95 m3/hr ventilator. It was able to cool the air drawn in from the outside by 7.6°C.